To investigate the significance of marketing mix (7P’s) that influences the consumer selection of shopping centers in Melaka Tengah / Stephanie Unyang George and Suliza Lambu - George, Stephanie Unyang; Lambu, Suliza (2014)
The paper assesses the significance of the 7p’s of marketing in influencing consumer selection of shopping center among consumer in Melaka Tengah. Research objective for this study is to define the significant relationship between independent variables (product, price, place, promotion, people, process and physical evidence) and dependent variable (customer selection of shopping center) and also to determine the most factors that highly influence consumer selection of shopping centers in Melaka Tengah. Data was gathered from a convenience sampling with 100 respondents using a questionnaire informed by 35-items construct based on the 7p’s of marketing amongst the consumer in Melaka Tengah. Descriptive analysis, coefficient correlation analysis and regression analysis were employed to analyze the data by using Statistical Package for Social Science (SPSS) 20 version. The result shows that all of the 7p’s of marketing has significant relationship with customer choice of shopping center in Melaka Tengah. However, among the 7p’s marketing, product is the most factors that highly influence consumer selection of shopping centers in Melaka Tengah.